Sexual selection drives asymmetric introgression in wall lizards - Geoffrey M. While; Sozos Michaelides; Robert J. P. Heathcote; Hannah E. A. MacGregor; Natalia Zajac; Joscha Beninde; Pau Carazo; Guillem Pérez i de Lanuza; Roberto Sacchi; Marco A.L. Zuffi; Terézia Horváthová; Belén Fresnillo; et al. (Ecology Letters, 2015)
Hybridisation is increasingly recognised as an important cause of diversification and adaptation. Here, we show how divergence in male secondary sexual characters between two lineages of the common wall lizard ( Podarcis muralis ) gives rise to strong asymmetries in male competitive ability and mating success, resulting in asymmetric hybridisation upon secondary contact. Combined with no negative effects of hybridisation on survival or reproductive characters in F1‐hybrids, these results suggest that introgression should be asymmetric, resulting in the displacement of sexual characters of the sub‐dominant lineage. This prediction was confirmed in two types of secondary contact, across a natural contact zone and in two introduced populations. Our study illustrates how divergence in sexually selected traits via male competition can determine the direction and extent of introgression, contributing to geographic patterns of genetic and phenotypic diversity.